Les remakes comme témoins de la poétique du cinéma d’horreur hollywoodien contemporain - David Roche (Mise au Point)
This articles focuses on the recent cycle of Hollywood remakes of American horror movies of the 1970s-1980s. Comparative analysis reveals the extent to which the big budget remakes of the 2000s testify to a homogenization of contemporary Hollywood horror aesthetics regardless of the subgenre. This standardization owes much, on the one hand, to the contemporary mainstream style David Bordwell has labeled “intensified contitnuity” and, on the other, to the tendency of taking the slasher, a subgenre that dominated the 1980s-1990s, as a model. This article emphasizes two consequences of this homogenization: first, it makes for an poetics that is not always coherent with the figure of horror represented in each film; and second it testifies to an impoverishment of formal options within each film, the remakes proposing overall less variation than the original films. The deficiencies of these films have thus less to do with their status as remakes as with their tendency to recycle hackneyed conventions. Particular attention is paid to Dawn of the Dead (Zack Snyder, 2004) and Halloween (Zombie, 2007).